2005
DOI: 10.4236/jmmce.2005.41005
|View full text |Cite
|
Sign up to set email alerts
|

Alteration Characteristics Of Ilmenites From South India

Abstract: Abstract:Two different placer samples from the Navaladi and Surungudi area of Teri, Tamilnadu, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Hugo et al (1991) discussed the alteration and petrographic studies of ilmenite present in the Holocene dunes of South Africa. Rao et al (2005) stated that the ilmenite deposits of south Tamil Nadu coastal areas are also altered along grain boundaries and fractures. This alteration leads to formation of leucoxene.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hugo et al (1991) discussed the alteration and petrographic studies of ilmenite present in the Holocene dunes of South Africa. Rao et al (2005) stated that the ilmenite deposits of south Tamil Nadu coastal areas are also altered along grain boundaries and fractures. This alteration leads to formation of leucoxene.…”
Section: Resultsmentioning
confidence: 98%
“…Chandrasekharan and Murugan (2001) stated that southern coastal Tamil Nadu, particularly from Navaladi to Tuticorin, has a rich content of garnet. Rao et al (2005) stated that the high concentration of heavy minerals occurring in the beaches may be ascribed primarily to the reworking of heavy-mineral-laden Quaternary sediments in the coastal plains that probably extend offshore and to the influence of coastal processes involving onshore, offshore and longshore movements, with their original source being the granulitic provenance comprising khondalite, charnockite and granitic gneisses. They also performed microscopic studies on heavy minerals along the study area and found that the placer ilmenite occurs mostly as sub-rounded to sub-angular grains, marked by numerous surface pits, etch marks or grooves, crescentic pits and mesh-like patterns.…”
Section: Resultsmentioning
confidence: 99%
“…i.e., ilmenite from below water table than the ilmenite from above water table, pre-and post-tsunamic ilmenite which supports dissolution and / or oxidation of iron from ilmenite in natural water or in acidic water leading to an enrichment of titanium and other elements in the residuum. This may be the main cause for ilmenite alteration [32] and the alteration products could be due to the exogenic processes that operated on these ilmenites after their release from the parent rocks [39]. The higher contents present in core ilmenite (BWT) is ascribed to the local concentration of such elements.…”
Section: Minor and Trace Element Concentrationmentioning
confidence: 99%
“…Teri sands are very lean placer deposits for heavy mineral concentration. The beach and in land placer deposits exhibit a considerable variation in mineralogy and chemical composition The literature reveals [1][2][3][4][5][6][7][8][9][10] that lot of research work carried out on Teri sands but most of the publications restricted to resource evaluation, geology, geochemistry, mineralogy etc. The general practice to recover Total Heavy Minerals from such a lean beach sand deposit containing 2-5% THMs is first concentrated to 20 -30% THMs on cone concentrators.…”
Section: Introductionmentioning
confidence: 99%